POPULATION AGING: AN INEVITABLE TREND AND GLOBAL CHALLENGE FOR PUBLIC HEALTH AND DEVELOPMENT - Thien Nhan, Nguyen (Journal of Health and Aging, 2025)
Population Aging is a global trend characterized by an increasing proportion of people aged 65 and over in the total population. This article analyzes the phenomenon of PA through a demographic lens, clarifying that aging is not solely the result of increased life expectancy, but also due to a prolonged period of below-replacement total fertility rate (TFR). Evidence from South Korea illustrates this dynamic: within just 60 years, the country transitioned from a nonaged society (1960) to a super-aged society (projected in 2027), with the consequence of a steep population decline starting in 2020. Vietnam, projected to become an ‘aged’ society by 2036 and a ‘super-aged’ society around 2060, must recognize emerging trends and underlying causes early to develop appropriate adaptation policies. Population Aging is not merely the outcome of medical advances and improved living conditions; it also reflects national governance decisions related to fertility, elder care, and sustainable human development. This article emphasizes the importance of monitoring TFR, the proportion of older adults, and the labor force in order to formulate responsive population policies in the context of rapidly advancing aging